Synthesis and Properties of Poly(p‐phenylene ethynylene)s with Oxidation‐ and Reduction‐Sensitive Moieties. Issue 11 (15th May 2013) - Schroeter, Michael; Behl, Marc; Kaiser, Christian; Lendlein, Andreas; Lendlein, Andreas
Abstract The synthesis of redox‐sensitive poly(p‐phenylene ethynylene)s (rsPPEs) bearing protected quinones in their backbone by the Sonogashira coupling reaction is described. The rsPPEs show excellent solubility in toluene, tetrahydrofurane, and chloroform. Cleavage of the protection group of the incorporated quinone moieties enables main‐chain conductive polymers having redox‐sensitive properties to be produced. These redox‐sensitive switches can be reduced and oxidized in solution, as well as in the solid state, accompanied by a change of the photoluminescence values. The processes occurring during oxidation and reduction are analyzed by UV–vis and photoluminescence spectroscopy and lead to a decrease of intensity of 80% during oxidation. Such multifunctional polymers may be useful for redox‐potential changing stimuli in biological systems.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>